Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.chemmater.6b02042
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a 4,9-Didodecyl Angular-Shaped Naphthodiselenophene Building Block To Achieve High-Mobility Transistors

Abstract: A new tetracyclic 4,9-dialkyl angular-shaped naphthodiselenophene (4,9-α-aNDS) was designed and synthesized. The naphthalene core in 4,9-α-aNDS is formed by the DBU-induced 6π-cyclization of an (E)-1,2-bis(3-(tetradec-1-yn-1-yl)selenophen-2-yl)ethene intermediate followed by the second PtCl 2 -catalyzed benzannulation. This synthetic protocol allows for incorporating two dodecyl groups regiospecifically at 4,9-positions of the resulting α-aNDS. An ordered supramolecular self-assembly formed via noncovalent sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 71 publications
(99 reference statements)
1
30
0
Order By: Relevance
“…In past several years, incorporating F atoms into conjugated backbone has emerged as a protocol to lower HOMO and LUMO energy levels and enhance the coplanarity of CPs, and various high‐mobility D–A CPs containing F atoms on either D or A units have been reported . In the current paper, we demonstrated that “multifluorination”, i.e., introducing F atoms onto both D and A units, not only can greatly lower the frontier orbital energy levels of the IID‐based polymers, but also can enhance the coplanarity of their conjugated backbones.…”
Section: Ofet Device Performance Data Of the Polymersmentioning
confidence: 63%
“…In past several years, incorporating F atoms into conjugated backbone has emerged as a protocol to lower HOMO and LUMO energy levels and enhance the coplanarity of CPs, and various high‐mobility D–A CPs containing F atoms on either D or A units have been reported . In the current paper, we demonstrated that “multifluorination”, i.e., introducing F atoms onto both D and A units, not only can greatly lower the frontier orbital energy levels of the IID‐based polymers, but also can enhance the coplanarity of their conjugated backbones.…”
Section: Ofet Device Performance Data Of the Polymersmentioning
confidence: 63%
“…Because traditional density functionals often fail in describing the dispersion force accurately, an additional dispersion correction ( E dis ) can be included in the above energy decomposition scheme with the aim of taking long-range interactions into consideration. 4856 Herein, numerous N , N ′-dialkyl-1,4,5,8-naphthalenetetracarboxylic diimides (R-NDIs) are chosen for the study, such as R = C 14 H 29 , 57 C 12 H 25 , 58 C 6 H 13 , 59 C 5 H 11 , 60 C 4 H 9 , 58 C 2 H 5 , 61 and 1-CH 3 C 6 H 12 58 (Scheme 2). The π- and lamellar stacking extracted from selected single-crystal structures are examined by ETS–NOCV.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with thiophene, the lower aromatic selenophene can increase the quinoidal resonance content, leading to an enhanced planarity of structures and lower optical bandgap. [ 110,111 ] The selenophene‐containing NFAs may be promising candidates for preparing efficient thick‐film OSCs. Hou and coworkers developed an efficient NFA, SeTIC4Cl, which contains selenopheno[3,2‐b]thiophene‐embedded seven‐heterocyclic fused ring core and dichlorinated end‐capped units.…”
Section: Categories Of Efficient Thick‐film Oscsmentioning
confidence: 99%